Guidelines for Developing Leadership in the 21st Century for School Administrators Under Khon Kaen Primary Educational Service Area Office Area 3 - Khulchai, Suphat; Poomkong, Somsak; Siripoonyanan, Tanasak (Journal of Buddhist Education and Research (JBER), 2025)
The research aimed to study 1) the current status, the desired status, and the leadership needs in the 21st century of school administrators under the Office of the Primary Educational Service Area, Khon Kaen Area 3 and 2) the guidelines for developing leadership in the 21st century of school administrators under the Office of the Primary Educational Service Area, Khon Kaen Area 3. This research was mixed-method research. The samples were 297 school administrators and teachers. The sample size was determined by opening the Krejci and Morgan table using stratified random sampling and simple random sampling. The research instruments were a 5-level rating scale questionnaire, a semi-structured interview form, an appropriateness and feasibility assessment form, the index of consistency was 0.8-1.00, the discrimination power of each item was between 0.45-0.89, and the reliability of the entire questionnaire was 0.99. The statistics used for data analysis were percentage, mean, standard deviation, the Priority of Needs Index (PNImodified), and content analysis. The results of the research were as follows: 1. The current situation is at a high level overall (x̄= 3.91) and when considering each aspect, it was found that all aspects were at a high level. The aspect with the highest average value was the aspect of creating and changing visions for a digital society (x̄= 3.95) and the aspect with the lowest average value was the aspect of developing expertise to become a professional ( = 3.88). 2. The desired state of academic leadership in the 21st century of school administrators under the Office of the Primary Educational Service Area 3, Khon Kaen, was at a high level overall (x̄= 4.79) and when considering each aspect, it was found that all aspects were at a high level. The aspect with the highest average value was the aspect of accepting new knowledge to create an intellectual society (x̄ = 4.86) and the aspect with the lowest average value was the aspect of creating and changing visions for a digital society (x̄ = 4.74). 3. The assessment of the needs of academic leadership in the 21st century of school administrators under the Office of the Primary Educational Service Area 3, Khon Kaen, found that overall, the need index value was PNImodified = 0.2249 and when considering each aspect Ranked from most to least, they are: Developing expertise to become a professional, with the highest need index (PNImodified = 0.2448), accepting new knowledge to create a society of knowledge, with the need index (PNImodified = 0.2398), promoting the use of information technology, with the need index (PNImodified = 0.2211), creating new innovations or services, with the need index (PNImodified = 0.2188), and creating and changing visions for a digital society, with the need index (PNImodified = 0.2000), respectively. 4. Guidelines for developing leadership in the 21st century for educational administrators Under the jurisdiction of the Office of the Primary Education Area, Khon Kaen Area 3, consisting of 5 areas and 15 approaches as follows: 1) Developing expertise to become a professional, with 3 approaches; 2) Accepting new knowledge to create a society of knowledge, with 3 approaches; 3) Promoting the use of information technology, with 3 approaches; 4) Inventing new innovations or services, with 3 approaches; and 5) Creating and changing visions for a digital society, with 3 approaches. Overall, the results of the evaluation of suitability were at the highest level, with an average of 4.93, and the results of the evaluation of feasibility were at the highest level, with an average of 4.77.